Mental health of agricultural adolescents and adults: Preliminary results of a five-year study - Rudolphi, Josie M.; Berg, Richard L. (Frontiers in Public Health, 2023)
Work-related stressors common to agriculture have been associated with adverse mental health outcomes among adult farmers and ranchers. However, the mental health status of agricultural youth is unknown. The objective of this study was to estimate the prevalence of symptoms of depression and anxiety among farm adults and their adolescent child and examine the correlation between symptoms of mental health conditions and financial indicators described in the Family Stress Model. Farm families were recruited to participate in online surveys by mail, email, and social media. One adolescent and at least one adult from each family were invited to complete on online survey. Where available, validated instruments were used to collect mental health, stress, family dynamics, and household financial variables. Descriptive statistics were used to describe sample demographics and prevalence of symptoms of depression and anxiety. Pearson correlations describe associations between variables within the Family Stress Model. 122 farm families completed the online survey. The mean age of farm parents was 41.4 years (SD= 4.4) and the mean age of farm adolescents was 15.4 (1.2). A majority of farm parents and farm adolescents were male. The sample was primarily white, non-Hispanic. Among farm parents and adolescents alike, 60% met the criteria for at least mild depression. Similarly, among adolescents, 45.1% met the criteria for Generalized Anxiety Disorder, as did 54.9% of adults. As a measure of economic hardship, per capita income by itself showed relatively low correlations, even with other economic measures (r = 0.11 with negative financial events, r = 0.20 with financial needs, r = 0.17 with financial situation, and r = 0.27 with debt). Parent depressed mood was in turn highly associated with adolescent depression (r = 0.83), social anxiety (r = 0.54) and generalized anxiety (r = 0.69). Preliminary analyses for study year 1 have shown the challenges of measuring economic pressures in the complex business of farming. Further, results show the strong association between parent and adolescent mental health and are promising for application of the full family stress model as we continue to accrue farm families into the study cohort.